Penerapan XP Dalam Pemenuhan Kebutuhan Sistem Yang Dinamis Pada Rancang Bangun Sistem Informasi Akuntansi Pendapatan Penjualan - Dominikus Riki Irawan; Nurfia Oktaviani Syamsiah (LPPM Universitas Bina Sarana Informatika, 2023)
Gathering system requirements is the most important thing in an information system development stage. As an initial stage it also determines the success of the next stage. But often when the system development process takes place there are changing needs so that it can make the system project go round and round at just one stage and the system fails to build. For this reason, an agile approach is used, namely Extreme Programming (XP), which by using XP the dynamic system needs can be better accommodated. One system that has dynamic needs is Sales Revenue SIA at a printing company in Pontianak City. With a small project team, XP is the main choice to be implemented in the system development process. As a result, a Sales Revenue Accounting Information System is obtained which has a user acceptance percentage of 96%.